Development of a Small-scale Supersonic Flight Experiment Vehicle as a Flying Test Bed for Future Space Transportation Research - MINATO, Ryojiro; UEBA, Masazumi; TANATSUGU, Nobuhiro; NAKATA, Daisuke; TAKAGI, Syohei; MIZOBATA, Kazuhide; HIGASHINO, Kazuyuki; HIGUCHI, Ken (TRANSACTIONS OF THE JAPAN SOCIETY FOR AERONAUTICAL AND SPACE SCIENCES, AEROSPACE TECHNOLOGY JAPAN, 2014)
Innovation in technologies for high-speed atmospheric flights is essential for establishment of both supersonic/hypersonic and reusable space transportations. It is quite effective to verify such technologies through small-scale flight tests in practical high-speed environments, prior to installation to large-scale vehicles. Thus we are developing a small-scale supersonic flight experiment vehicle as a flying test bed. Several aerodynamic configurations are proposed and analyzed by wind tunnel tests. A twin-engine configuration with a cranked-arrow main wing is selected as the baseline of the first generation vehicle. Its flight capability is predicted by point mass analysis on the basis of aerodynamic characterization and propulsion performance estimation. In addition, a prototype vehicle with an almost equivalent configuration and dimension is designed and fabricated for verification of the subsonic flight characteristics of the experiment vehicle. Its first flight test is carried out and good flight capability is demonstrated. Furthermore a revised aerodynamic configuration with an air-turbo ramjet gas-generator cycle (ATR-GG) engine is being designed for the second generation design with improvement in flight capability at higher Mach numbers. Development of the engine, airframe structure, and autonomous guidance/control system is underway. This prospective flight experiment vehicle will be applied to flight verification of innovative fundamental technologies for high-speed atmospheric flights such as turbo-ramjet propulsion with endothermic or biomass fuels, MEMS and morphing techniques for aerodynamic control, aero-servo-elastic technologies, etc.